Dyskursywne (re)konstruowanie charyzmy. Przypadek Lecha Wałęsy - LIPIŃSKI, Artur (Przegląd Politologiczny, 2018)
The paper analyzes the discursive reconstruction of L. Wałęsa’s charisma by the Gazeta Wyborcza newspaper in response to S. Cenckiewicz and P. Gontarczyk’s book entitled SB a Lech Wałęsa. Przyczynek do biografii [The secret police and Lech Wałęsa. Addendum to a biography]. The paper uses the methodology of interpretative research which emphasizes the role of meaning for the social and political construction of reality. Inspired by the theoretical and methodological proposals of discourse analysis it examines the mechanisms used to reconstruct Lech Wałęsa’s charismatic identity in response to a book that undermines his social image. These attempts also involve the construction of individual identity, in the case under analysis, the identity of historians and authors of the book who are responsible for undermining this image. Therefore, the paper also attempts to analyze media representations of S. Cenckiewicz and P. Gontarczyk. Attention is primarily focused on the key actors, on the features attributed to them and related argumentative strategies understood as a more or less intentional plan of discursive practices adopted in order to achieve defined social, political, linguistic or psychological purposes.